Methods and tools of formation of general indexes for automation of devices in rehabilitative medicine for post-stroke patients - Trunov, Alexandr; Beglytsia, Volodymyr; Gryshchenko, Gennady; Ziuzin, Viktor; Koshovyi, Vitalii (Eastern-European Journal of Enterprise Technologies, 2021)
The current processes of recovery of post-infarction and post-stroke patients in the context of the establishment of the institution of family doctors and insurance medicine are considered. It was proposed to introduce modules for automation of recovery devices (MARD) to ensure procedures, quality of life and reduce labor costs during the period of long-term recovery. The forms of presentation of the model of the integral indicator are substantiated, which, in accordance with the requirements of the Ministry of Health, assesses the generalized indicator of the patient’s statement (GIPS), the quality of medical services and increases the efficiency of data compression. A consistent application of two Euclidean norms is proposed, which leads indicators of dissimilar physical nature to a limited metric space. The relationship between the lower and upper bounds of the GIPS, the error, the width of the sliding window, and the values of the derivatives was established on the basis of the Taylor series expansion, geometric inequality and limited space. The model for evaluating the GIPS as a lower bound and the method for generating information about its properties are substantiated. A three-level comparator is applied and an vector- indicator (VI) is introduced as an informational addition to the time series. Additional capabilities for intelligent analysis are demonstrated. The model of GIPS through VI is presented. The examples of VI values are used to demonstrate its applicability to the intelligent analysis of the recovery process. Openness, accessibility, transparency of GIPS and VI as tools of KIT is implemented by the princes of public administration (PA) by reducing it to quantitative control and comparison if there are quantitative and qualitative indicators in the list. VI, sliding windows, as PA and KIT tools in software (SW) for a diagnostic conclusion and correction of the course of procedures, are numerically investigated. It is demonstrated on examples of a numerical experiment with software how the combined application of the method for calculating the GIPS and VI effectively affects the compression ratio, increasing it to 60–75 %